Gastrointestinal Bleeding: a Cardiologist's Point of View - O. V. Averkov; L. N. Mishchenko (Рациональная фармакотерапия в кардиологии)
Oral anticoagulant therapy is widely used in different patients for the prevention and treatment of thromboembolic events: in atrial fibrillation, deep vein thrombosis/pulmonary embolism, acute coronary syndrome, in the early postoperative period after orthopedic surgery. Nowadays it is possible to use vitamin K antagonists (warfarin) as well as direct oral anticoagulants (DOAC): dabigatran, rivaroxaban, apixaban and edoxaban. The mai complication of any anticoagulant therapy is bleeding (gastrointestinal, intracranial, etc.), which seriously limits its usage. In this review the incidence of gastrointestinal bleeding (GIB) associated with oral anticoagulants intake was analyzed according to the results of both large randomized and postregistration trials. Furthermore, the effect of age on the risk of GIB development is discussed, and also aspects of the pathophysiology of gastrointestinal mucosa lesions in patients taking DOAC are considered.